Exploring the use of resources to support gender equality in Australian workplaces. (1st January 2019) - Nally, Taylor; Taket, Ann; Graham, Melissa
Abstract: Issue addressed: Numerous resources exist to support workplaces to undertake gender equality work; however, it is often unclear which existing resources are being utilised by Australian workplaces. One group that can provide insight into the use of existing resources is the professionals who have undertaken gender equality work in their organisation. Methods: Purposive sampling was used to identify informants with experience undertaking gender equality work. A sample of 12 informants was recruited from five employment sectors: five informants from the women('s health sector; two from other organisations in the health sector; three from local government; and one each from manufacturing and education. One in‐depth semi‐structured interview was conducted with each informant. Interview transcripts were analysed using thematic analysis. Results: Four themes emerged from data analysis: "Organisational Context, " "Legitimising Gender Equality Work, " "Demystifying Gender Equality" and "Embedding Gender Equality into the Workplace." Mechanisms such as drawing on the evidence base, developing internal communications strategies, establishing a working group, undertaking training, conducting an audit, and reviewing policies and procedures were used to embed gender‐based considerations into the workplace. A range of resources to underpin most of these approaches was discussed by informants. Conclusions: Informants had a sound understanding of approaches they could use to address existing gender inequality; however, they did not always utilise existing resources to support them to undertake their chosen approach. So what?: A clearer online database needs to be established to allow workplaces to access a compilation of existing resources and any evaluation on their use.